Antibacterial and physical properties of ZnO with pH-sensitive morphology. Issue 17 (21st November 2016) - Pholnak, Chat; Lertworapreecha, Monthon; Sirisathitkul, Chitnarong; Suwanboon, Sumetha
ABSTRACT: The variation in morphology of zinc oxide (ZnO) with the pH of 0.05 M Zn(NO3 )2 and 1.00 M NaOH aqueous solutions is demonstrated. Microstructured ZnO ranges from cuboid to spindle as the pH is reduced from 12 to 9. The ratio of visible-to-UV peak from photoluminescence spectra is also decreased, whereas the energy gap calculated from UV-Vis spectra remains comparable. Furthermore, nanospheroids and microellipsoid are, respectively, obtained when the molar concentration of NaOH is reduced to 0.20 and 0.10 M for the synthesis with the pH of 7. Due to their large surface-to-volume ratio, these ZnO nanospheroids exhibit a higher antibacterial activity than that of commercial ZnO in the disc diffusion method. According to this method as well as the minimal inhibitory concentration measurement, the effectiveness is substantial in the case of Staphylococcus aureus and Escherichia coli . By contrast, the inhibitions of Klebsiella pneumoniae, Salmonella typhimurium and Pseudomonas aeruginasa are barely observed.